Editorial: helminth biodiversity - Simões, Raquel de O. (2023)
The aim of this Research Topic is to broaden and deepen the knowledge about helminths in wildlife or domestic hosts around the world focusing on the contribution to the taxonomic groups, ecology, phylogenetic, and biology. Thus, a multidisciplinary approach is given and can be used as a guide for scientific information. In this special collection, there are seven papers covering the differents aspects.